Between Object and Subject: Multiple Approaches to a Prehistoric Human-Shaped Pot from Romania - Opriș, Vasile; Manea, Bogdan; Lechintan, Mircea; Bugoi, Roxana; Constantin, Florin; Ignat, Theodor; Lazar, Catalin (Documenta praehistorica, 2022)
The current paper aims to reveal the potential of combining multiple approaches (techno-functional analysis, experimental archaeology, and X-ray Computed Tomography) when it comes to studying unique earthenware artefacts, such as the prehistoric human-shaped pot discovered within the tell settlement from Sultana-Malu Rosu (Romania), that belongs to the Kodjadermen-Gumelnita-Karanovo VI civilization (KGK VI) which thrived during the 5th millennium BC. This human-shaped pot, also known as ‘The Goddess of Sultana’, is an emblematic artefact that fascinates with its shape, gestures, and decoration. It was apparently made from a standard clay paste recipe and using basic forming techniques, with little care for the internal surface. This vessel also has several hidden cracks and some manipulation traces on its backside. In order to explore its relevance, our approach to this particular human-shaped pot included the use of archaeological data in correlation with other techniques in order to decipher the manufacturing process for such vessels, the possible way of using them, but also the meanings that they might have had for past human communities.